PENINGKATAN SUMBER DAYA MANUSIA MELALUI KKN POSDAYA BERBASIS MASJID DI DUSUN PASINAN KECAMATAN SINGOJURUH BANYUWANGI - Ingkan Prio Manunggal (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2018)
Mosque-based Posdaya is a community movement by refreshing social capital, strengthening commitments and networking based on local wisdom and potential carried out by the community, by the community and for the community. The reason the mosque is used as a place of axis in empowerment this time is that worship is not only fulfilling the obligation to pray 5 times, but how Muslims are able to escape poverty, here the concept of development becomes integrative between the world and the hereafter. The concept of poverty alleviation is not only the duty of the government but is the responsibility of the mosque and the surrounding community. Therefore Posdaya mosque is formed as a forum for the community through mosque media to equally help overcome the problems faced by families through work programs in the education sector in the entrepreneurship sector, the religious sector and the arts sector.